2017
DOI: 10.3928/01484834-20170817-03
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Short-Term Study Abroad Experiences on Community Health Baccalaureate Students

Abstract: Student perceptions of culture demonstrated progression through previously described stages of cultural competence. Relatively novel themes regarding community relationships, perceptions of health and happiness, and adaptability suggest additional value of this short-term study abroad experience for nursing students. [J Nurs Educ. 2017;56(9):528-533.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…Learning outcomes for international clinical placements, described in the literature have emphasized the observed benefits of promoting cultural awareness through challenging students in a culturally diverse environment whilst also assisting them to achieve clinical proficiency (Phillips et al, 2017;Maltby et al, 2016;Ng, Goddard, Gribble & Pickard, 2012). Additionally, such placements are believed to provide nursing students with the opportunity to increase their knowledge of, and ability to, communicate across cultural boundaries; a skill that has important implications for their ongoing professional practice (Smith-Miller, Leak, Harlan, Dieckmann & Sherwood, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Learning outcomes for international clinical placements, described in the literature have emphasized the observed benefits of promoting cultural awareness through challenging students in a culturally diverse environment whilst also assisting them to achieve clinical proficiency (Phillips et al, 2017;Maltby et al, 2016;Ng, Goddard, Gribble & Pickard, 2012). Additionally, such placements are believed to provide nursing students with the opportunity to increase their knowledge of, and ability to, communicate across cultural boundaries; a skill that has important implications for their ongoing professional practice (Smith-Miller, Leak, Harlan, Dieckmann & Sherwood, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although these were relatively short-term placements a study by Phillips et al (2017), of American Baccalaureate students travelling to Ghana, has reported that longer placements are not necessarily required to see a shift in students' attitudes away from ethnocentrism towards the beginnings of increased cultural sensitivity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was somewhat surprising as friendship formation is not typically mentioned in the literature as an anticipated benefit from SA. Similarly, Philips et al (2017) found returning SA nursing students viewed the personal international relationships they had developed as an unexpected outcome and expressed the desire to continue to grow these friendships. Finally, the anticipated benefit of gaining international nursing experience (Kent-Wilkinson et al, 2015) was achieved for our participants who strongly valued their exposure to a different health care context.…”
Section: Discussionmentioning
confidence: 99%
“…Student experiences can differ by the length of an exchange program, the destination, whether in a group or individually, by how much the exchange is facilitated, and description of the learning outcomes to be achieved (Phillips, Bloom, Gainey, & Chiocca, 2017). The most common length is short-term stays of 1-4 weeks; however, institutions might exchange students for a clinical placement or theoretical courses, or for a semester-long placement as is the often the case with Swedish students (Nilsson et al, 2014).…”
Section: Length and Feasibility Of Exchangesmentioning
confidence: 99%